Implementation of International Arbitration Awards in Indonesia from the Perspective of Legal Value Theory - Sari, Niken Junika; Zulfikar, Ahmad Arif; Dorlah, Sulaiman (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2024)
Establishing an arbitral institution aims to resolve business disputes swiftly and conclusively, with arbitration's finality and binding nature being key principles. However, Indonesian arbitration law requires exequatur from the Central Jakarta District Court to enforce an international arbitration award, leading to delays and complications. A notable instance involved the annulment of an international arbitration award due to ambiguous norms. This study employs a normative research methodology with a theoretical approach to highlight the misalignment between international arbitration awards in Indonesia and Gustav Radbruch's Theory. The findings indicate that the lack of a balanced approach to justice, conflicting norms resulting in legal uncertainty, and the failure to provide benefits to all parties contribute to this misalignment. According to Radbruch, law aims to achieve justice, legal certainty, and expediency, with clear and logical provisions necessary for legal certainty and laws serving the diverse interests of all parties for expediency. The issuance of the Republic of Indonesia Supreme Court Regulation No. 3 of 2023 represents an effort to improve Indonesia's arbitration law. Revising Indonesian arbitration law is essential to align it with Radbruch's Theory, ensuring justice, legal certainty, and expediency in international arbitration awards.